2018
DOI: 10.1002/pmic.201700446
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling Human Cardiac Fibroblast Membrane Proteome

Abstract: Cardiac fibroblasts (CFs) are one of the main cell populations in the heart and play important roles in tissue homeostasis and myocardial fibrosis. The study of these cells has been hampered by the lack of reliable membrane markers: none of the antigens currently used for characterization and isolation of CFs is unique for this cell type. This issue has also raised doubts regarding a distinct identity of cardiac fibroblasts when compared to other myocardium cell populations with similar morphologies. In this w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…PDGFRα is expressed by widely distributed non-vascular interstitial fibroblasts ( Ivey and Tallquist, 2016 ; Sebastiao et al, 2018 ) including a subpopulation of cells marking enriched MSC populations in all organs/tissues ( Farahani and Xaymardan, 2015 ; Ivey and Tallquist, 2016 ). Detailed single-cell RNA (scRNA) analysis has shown that while the PDGFRα cells in the mouse hearts are mostly fibroblastic in nature, a small population co-expresses endothelial marker CD31, and a further minor population co-expresses macrophage markers.…”
Section: Role Of Platelet-derived Growth Factor In Cardiac Injury Modelsmentioning
confidence: 99%
“…PDGFRα is expressed by widely distributed non-vascular interstitial fibroblasts ( Ivey and Tallquist, 2016 ; Sebastiao et al, 2018 ) including a subpopulation of cells marking enriched MSC populations in all organs/tissues ( Farahani and Xaymardan, 2015 ; Ivey and Tallquist, 2016 ). Detailed single-cell RNA (scRNA) analysis has shown that while the PDGFRα cells in the mouse hearts are mostly fibroblastic in nature, a small population co-expresses endothelial marker CD31, and a further minor population co-expresses macrophage markers.…”
Section: Role Of Platelet-derived Growth Factor In Cardiac Injury Modelsmentioning
confidence: 99%
“…The hCPCs employed in this work are not the same population involved in this controversy and were isolated and cultured using a different protocol (Patent WO2014141220A1), which was also used for the isolation of the hCPC population recently evaluated for the allogeneic treatment of AMI in CAREMI clinical trial (NCT02439398). Importantly, these cells were already extensively characterized at the immunomodulatory [1417], total proteome [18], membrane proteome [19, 20], and secretome [21] levels. The regenerative benefit of these cells was studied in vivo in pig AMI animal model [22, 23].…”
Section: Introductionmentioning
confidence: 99%
“…miRNA-1306-5p is known to be released by the myocardium, and its circulating levels are considered a biomarker of HF. 43 We found that miRNA-1306-5p is expressed in human SAN fibroblasts as well, with higher levels in untreated non-HF SAN fibroblasts. Network analyses also showed that many of the significantly different SAN miRNAs paired inversely with selected ECM and profibrotic genes, which predicted potential miRNA-mediated regulation of these genes and SAN fibrosis (Figure 7).…”
Section: Discussionmentioning
confidence: 67%